Environmental and socio-economic effects associated with the planting of Atriplex nummularia Lindl. (Oldman saltbush) in the Karoo - Hobson, Colin Desmond (Rhodes University, Faculty of Science, Botany Department, 1991)
This study examines the environmental and socio-economic effects associated with the planting of Atriplex nummularia Lindl. (Oldman saltbush) in the karoo. This is the first study of its kind on oldman saltbush and serves as an important scoping exercise in assessing the impact of saltbush on its surrounds and in identifying additional aspects which require investigation. The environmental parameters investigated include microclimatic effects, soil induced changes, salinity effects on the germination of selected karoo species and compositional changes in the indigenous plant community within a saltbush plantation. When compared to indigenous karoo plant species oldman saltbush is found to ameliorate soil temperatures and increase surface soil salinity (specifically sodium chloride), on an individual plant basis. Salinity is shown to have a differential effect on the germination of selected karoo shrubs. The indigenous plant community within a forty year old saltbush plantation is impoverished with both density of individuals and species richness being markedly reduced. Saltbush is identified as an unsuitable nurse plant for the majority of karoo shrubs. Farm size in relation to both actual and intended area established to saltbush is considered. The area of saltbush already established in the karoo is considered too insignificant to have any wide socio-economic impact. Farmers who intend planting large areas of their farms to saltbush are in the minority. It is those farmers who already have some saltbush planted, who intend planting more. Ecologically based management guidelines are presented, suggesting practices which minimize the detrimental effects of saltbush on soil salinity and the indigenous plant community. These guidelines are practical and in keeping with the overall objectives of optimum resource utilisation and the national grazing strategy for South Africa.
Keywords: Botany, Economic; Plant introduction -- South Africa -- Karoo; Plants, Cultivated